2010
DOI: 10.1016/j.surg.2009.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Clostridium difficile-associated diarrhea

Abstract: Background-Abdominal surgery is thought to be a risk factor for Clostridium difficile-associated diarrhea (CDAD). The aims of this study were to discern pre-operative factors associated with postsurgical CDAD, examine outcomes after post-surgical CDAD, and compare outcomes of postsurgical vs. medical CDAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 38 publications
5
36
0
2
Order By: Relevance
“…Table 1 shows the main characteristics of the included studies. The majority of the studies were conducted in North America (n = 26) [13,14,[16][17][18][19][20]23,[25][26][27]31,33,34,38,40,41,[43][44][45][46][47][48][49][50][51], whilst 7 were conducted in Europe (mainly in the UK) [21,22,[28][29][30]32,35]. One more study included patients from North America and the UK [15], four from Asia (South Korea and Taiwan) [36,37,39,42] and one from Argentina [24].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the main characteristics of the included studies. The majority of the studies were conducted in North America (n = 26) [13,14,[16][17][18][19][20]23,[25][26][27]31,33,34,38,40,41,[43][44][45][46][47][48][49][50][51], whilst 7 were conducted in Europe (mainly in the UK) [21,22,[28][29][30]32,35]. One more study included patients from North America and the UK [15], four from Asia (South Korea and Taiwan) [36,37,39,42] and one from Argentina [24].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…In 5 of the 18 non-profit-funded studies the authors reported having received grants from pharmaceutical companies [19,25,27,34,49], as did 1 of the 11 studies for which no funding was reported [31]. In 14 studies the authors reported no conflicts of interest [13,22,24,29,30,32,33,40,41,[43][44][45]48,50], whilst in the remaining 9 studies no data regarding conflict of interest were reported [26,[35][36][37]39,42,46,47,51].…”
Section: Figurementioning
confidence: 99%
“…However newer studies show that there was no clear association between overall cephalosporin usage (or any cephalosporin) and CDI incidence [17]. The prophylactic dose given immediately before surgery is associated with dramatically reduced rates of wound infection and post-operative sepsis [18]. It is likely that any slightly increased risk of post-operative CDI associated with such prophylactic use of antibiotics would be outweighed by benefit [8].…”
Section: Discussionmentioning
confidence: 99%
“…Die PPI-induzierte Säuresuppression stellt einen Risikofaktor für die Clostridium-difficile-assoziierte Diarrhö (CDAD) bei hospitalisierten Patienten dar [2,46].…”
Section: Clostridium-difficileassoziierte Diarrhöunclassified
“…Dies ist auch für die postoperative CDAD in einem großen chirurgischen Patientenkollektiv gezeigt worden [46]: Die analysierte Serie umfasste 3904 Patienten mit abdominalchirurgischem Eingriff, von denen 46 postoperativ eine CDAD erlitten hatten. Im Vergleich zu allen Patienten hatten die Patienten mit CDAD (neben höherem Lebensalter, häufigerer Antibiotikaeinnahme und mehr vorangegangenen Krankenhausaufenthalten) auch häufiger eine PPI-Medikation im Vergleich zum Gesamtkollektiv (28,3% vs. 10,0%, p<0,001).…”
Section: Clostridium-difficileassoziierte Diarrhöunclassified